2019
DOI: 10.32942/osf.io/k72ye
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local forest structure variability increases resilience to wildfire in dry western U.S. coniferous forests

Abstract: A ‘resilient’ forest endures disturbance and is likely to persist. Resilience to wildfire may arise from feedback between fire behaviour and forest structure in dry forest systems. Frequent fire creates fine‐scale variability in forest structure, which may then interrupt fuel continuity and prevent future fires from killing overstorey trees. Testing the generality and scale of this phenomenon is challenging for vast, long‐lived forest ecosystems. We quantify forest structural variability and fire severity acro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…Partnership built on an integrated all-lands approach The Rogue Basin Strategy articulated an integrated, scalable, social-ecological approach for considering management options using structured decision making (Thompson et al 2013b;Tulloch et al 2015) of This spatial action mapping has begun to guide collaborative management at multiple spatial scales (Figure 1) with formation of more effective land management partnerships and growing co-investment in shared objectives ( Wildfire risk reduction and benefits of an all lands approach Fire weather can overwhelm individual fuels treatments, but our modeled results are consistent with empirical studies that have found strategic fuel treatments that promote structural heterogeneity at multiple scales in advance of wildfire can increase forest resistance and resilience to wildfire (Koontz et al 2020;Lydersen et al 2017;Prichard et al 2020;Stevens et al 2014;Tubbesing et al 2019). Both the MF and AL scenarios significantly reduced wildfire risk overall, but the AL scenario reduced risk by an additional 52%, with a 20% increase in treatment footprint on non-federal lands.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Partnership built on an integrated all-lands approach The Rogue Basin Strategy articulated an integrated, scalable, social-ecological approach for considering management options using structured decision making (Thompson et al 2013b;Tulloch et al 2015) of This spatial action mapping has begun to guide collaborative management at multiple spatial scales (Figure 1) with formation of more effective land management partnerships and growing co-investment in shared objectives ( Wildfire risk reduction and benefits of an all lands approach Fire weather can overwhelm individual fuels treatments, but our modeled results are consistent with empirical studies that have found strategic fuel treatments that promote structural heterogeneity at multiple scales in advance of wildfire can increase forest resistance and resilience to wildfire (Koontz et al 2020;Lydersen et al 2017;Prichard et al 2020;Stevens et al 2014;Tubbesing et al 2019). Both the MF and AL scenarios significantly reduced wildfire risk overall, but the AL scenario reduced risk by an additional 52%, with a 20% increase in treatment footprint on non-federal lands.…”
Section: Discussionsupporting
confidence: 76%
“…Historically, fires maintained a resilient forest landscape of selfreinforcing patches that perpetuated an array of fire regimes, including significant lowmoderate severity (Hessburg et al 2019). Under some conditions, low-moderate severity fire can still restore or maintain landscape-scale patterning and resilient forest conditions (Koontz et al 2020;Meyer 2015) and support high species diversity (Richter et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given this broad consensus in the scientific literature, some authors suggest that forest thinning should be considered in the context of wildfire hazard abatement, ecological restoration and adaptation, and revitalization of cultural burning (Lehmkuhl et al 2007, Hessburg et al 2015. Where restoring resilient forest composition and structure and reducing future wildfire hazard are goals of management (Koontz et al 2020), combined thinning and burning approaches will provide ecological and wildfire-risk reduction benefits (Knapp et al 2017).…”
Section: Accepted Articlementioning
confidence: 99%
“…There have been an increasing number of studies of how interactions among fire, herbivores, and vegetation in these ecosystems influence the landscape‐scale heterogeneity of tree‐grass ratios (Higgins et al 2000, Sankaran et al 2008, Holdo et al 2009, Hempson et al 2019, Johansson et al 2020) and grass fuel loads (Bielski et al 2018, Starns et al 2019). Fewer examine how these interactions affect fine‐scale landscape heterogeneity (Blackhall et al 2017), despite the assertion that spatial heterogeneity in turn engenders landscape‐level diversity (Pickett and Cadenasso 1995, Stein et al 2014) and resilience to future disturbance (Koontz et al 2019). These questions are made even more critical by increasing global encroachment of woody species into grassland ecosystems, reducing livestock production and wildlife habitat (Wilcox et al 2018, Buisson et al 2019).…”
Section: Introductionmentioning
confidence: 99%